Una nueva especie costarricense del género Amyris P. Browne (Rutaceae) - Gómez-Laurito, Jorge; Jiménez, Quírico (Lankesteriana: International Journal on Orchidology, 2016)
A new species of Amyris P. Browne (Rutaceae) with large opposite pinnate leaves is described from the central and southern Pacific region of Costa Rica.